Insight into the Electrical Double Layer of Ionic Liquids Revealed through Its Temporal Evolution - Han, Mengwei; Kim, Hojun; Leal, Cecilia; Negrito, Maelani; Batteas, James D.; Espinosa-Marzal, Rosa M. (WILEY, 2020)
Ionic liquids (ILs) are proposed as potentially ideal electrolytes for use in electrical double layer capacitors. However, recent discoveries of long-range electrostatic screening in ILs have revealed that this understanding of the electrical double layer in highly concentrated solutions is still incomplete. Through precise time-dependent measurements of wide-angle X-ray scattering and surface forces, novel molecular insight into their electrical double layer is provided. An ultraslow evolution of the nanostructure of three imidazolium ILs is observed, which reflects the reorganization of the ions in confined and unconfined (bulk) states. The observed phase transformation in the bulk consists of the ILs ordering over at least 20 h, reflected in an expansion or contraction of the spacing between the ions organized in domains of approximate to 10 nm. This transformation justifies the evolution of the electrical double layer measured in force measurements. Subtle differences between the ILs arise from the intricate balance between electrostatic and non-electrostatic interactions. This work reveals a new time scale of the evolution of the IL structure and offers a new perspective for understanding the electrical double layer in ILs, with implications on diverse areas of inquiry, such as energy storage, lubrication, as well as micro- and nanoelectronics devices.
Keywords: SURFACE FORCES APPARATUS; HYDROGEN-BONDS; INTERFACE; ELECTROLYTES; DYNAMICS; LENGTH; NANOSTRUCTURE; FILMS; TIME